Stand and deliver : how to become a masterful communicator and public speaker - Dale Carnegie Training (Firm) (New York, NY : Simon & Schuster, 2011)
Stand and Deliver gives you everything you need to know to become a poised, polished, and masterful communicator. It reveals the techniques that have worked for countless great speakers throughout history. In this book you will learn how to prepare properly for a presentation, develop and project your own unique style, overcome stage fright, and win any audience in one minute. Packed with tips, strategies, and real-life examples, including case studies of some of the world's great orators, Stand and Deliver is the definitive guidebook for public speaking.
Keys to high impact delivery -- What every listener really wants, what every speaker needs to know -- Case study : Winston Churchill -- Overcoming stage fright : "Nothing to fear but fear itself" -- Using humor effectively -- Stories and self-revelation : how to win attention and respect -- Case study : Eleanor Roosevelt -- Motivating your listeners to action -- Winning the first minute : making a positive impression -- The power of persuasion, part one -- The power of persuasion, part two -- Creativity and the magic formula -- Case study : Franklin Delano Roosevelt -- Dealing with questions and answers -- How to conclude a presentation -- Case study : Sports talk.
"A Touchstone book."
Keywords: Public speaking; Persuasion (Rhetoric)